Democratic Dilemmas of Multilevel Governance
XIX, 255 p.
Keywords: Focusing on the EU, this volume, with a combination of theoretical perspectives and empirical research, examines the problems multilevel governance causes for democratic legitimacy by placing it in a comparative and theoretical context, and explore how challenges faced by the EU compare with those faced by traditional federal systems worldwide.